Clinical Presentation of Dengue Fever Cases from Islamabad: A Retrospective Study - Muhammad Zeeshan, Muhammedwaleed Mukhtar, Javeria Sajjad, Misbah Salim, Maqsood Ahmad, Usman Amjad, Shajee Ahmad Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dengue fever is a mosquito-borne viral infection caused by the virus aedesaegypti.InPakistan, a major dengue epidemic appeared in 2011. The objective of the present study is to observe the clinical presentations of dengue fever in a recent outbreak in 2022. Method: The retrospective study was performed on 174 patients diagnosed with dengue fever aged 13 to 60 years. Data regarding age, gender, and clinical symptoms i.e. fever, myalgia, nausea, vomiting, abdominal pain. Results: Most of the patients were from the 18-25 years age group. with a greater number of males compared to females. The common presentation of dengue fever was fever and myalgia, observed in 92% and 62% of the patients, respectively. A platelet count of less than 1,00,000 was observed in 85% of patients, whereas decreased total leukocyte count (TLC) and hematocrit were observed in 50% and 46.8% of patients, respectively. Practical Implication: On the documentation, reporting, and management of these co-morbidities, there were no local regulations accessible. This study determined the frequency of co-morbidities in dengue patients and analyse the early dengue case presentations. Conclusion: Patients presenting with fever, hemorrhagic symptoms, or signs of plasma leakage should be promptly suspected, timely diagnosed, and managed on the grounds of dengue fever. Keywords: Dengue fever, Viral Infection, Diagnosis, Morbidity, Mortality Retrospective study